Sahodaran Ayyappan : towards a democratic future life and select works - Sekhar, Ajay, 1976-; Ayyappan, Ke., 1889-1968. (Calicut : Other Books, 2012)
Biography and selected works of Ke. Ayyappan, 1889-1968, social reformer cum poet from Kerala.
Includes bibliographical references (pages 260-262) and index.
Keywords: Ayyappan, Ke., -- 1889-1968.; Social reformers -- India -- Kerala -- Biography; Authors, Malayalam -- 20th century -- Biography